Evaluation of Protective Properties of Commercially Available Medical Helmets: Are Medical Helmets Protective?. Issue 1 (17th January 2022) - Barrett, Blake; Peterson, Matthew J.; Phillips, Sam L.; Lloyd, John; Cowan, Linda; Friedman, Yvonne; Ramaiah, Padmaja; Neily, Julia; Bulat, Tatjana
Abstract : Objectives: The aims of the study were to evaluate and to compare protective properties of commercially available medical helmets for a set of standardized head injury risk measures. Methods: Eleven helmet types were evaluated to represent the variety of commercially available medical helmet designs and manufacturers. A test mannequin and sensor apparatus were used to simulate a backward-standing fall. The head/neck size, mass, and "standing" height of the mannequin (5′9″) were representative of a 50th percentile male. A triaxial array was placed at the head center of mass to position 3 linear accelerometers and 3 angular rate sensors. Data were collected for 5 single trials for each helmet, as well as 5 repeated trials. Five trials were also collected with no helmet scenarios. Three head injury risk measures were examined (linear acceleration, angular acceleration, and head injury criterion). Data were analyzed by clinical cutoff thresholds and continuous values. Results: Helmets varied in their performance across head injury risk measures. All helmets provided higher levels of protection compared with no helmet scenarios. No helmets were protective for subdural hematoma (measured by angular acceleration). All helmets lost protective properties with repeated falls. Results for skull fracture risk were inconsistent between linear acceleration and head injury criterion injury risk measures. Conclusions: No helmets were protective across all head injury risk measures. Medical helmets may reduce some fall injury severity but may not prevent all types of head injury. All helmets exhibited worsening of protective properties with repeated falls. We recommend medical helmets be replaced after each fall incident where the helmet impacts another surface.